GONADOTROPHIC HORMONE CONCENTRATION AND LITTER SIZE IN EWES IMMUNIZED AGAINST ANDROSTENEDIONE - KUMAR, R ANIL; CHANDRAHASAN, C; SELVARAJU, M (The Indian Journal of Animal Reproduction, 2022)
Immunization against androstenedione is one of the methods of improving the litter size in sheep. The level of gonadotrophin has been said to be controlling factor for ovulation rate. An attempt was made to correlate the level of gonadotrophic hormones with litter size in ewes. Ninety parous healthy Nilagiri (45) and Sandyno (45) ewes were selected and allotted to 3 treatment groups of 15 ewes in each breed (AF-Androstenedione immunogen-full dose, AH-half dose and CC-control group). The ewes from AF and AH groups were injected with androstenedione immunogen (Ovastim, Virbac (Australia) Ltd,) at 8 and 4 weeks before the start of breeding season. Blood samples were collected during Early Follicular Phase (EFP), Late Follicular Phase (LFP) and Mid Luteal Phase (MLP) of the estrous cycle. LH and FSH concentrations were analysed by double antibody radioimmunoassay (RIA). Among the immunized ewes the litter size was higher in Sandyno AF ewes (1.73 ± 0.11) and Nilagiri AH ewes (1.60 ± 0.13). The concentration of LH was significantly higher in immunized groups. The level of LH during EFP (3.91±0.29 çg/ml) was significantly higher than LFP (2.77±0.36 ηg/ml) and MLP (2.19±0.28 ηg/ml). The FSH concentration was higher in EFP (31.49±2.00 ηg/ml) and a sharp decline in LFP (22.70±2.45 ηg/ml) and again reached the highest value in MLP (33.01±1.85 ηg/ ml). The Nilagiri ewes (30.28±1.73 ηg/ml) had higher FSH concentration than Sandyno ewes (27.85±1.73 ηg/ml). The increased plasma LH concentration could be a reason for increased litter size in immunized ewes.